Study on the Performance of Ball Mill with Liner Structure based on DEM - Zhanfu Li; Yaokun Wang; Kunyuan Li; Wenyu Lin; Xin Tong (Institute for Research and Community Services, Institut Teknologi Bandung, 2018)
This study used the discrete element method (DEM), which is effective and popular for solving the problem of granular systems simulating the motion of particles in a ball mill in different structural forms and at different rotational speeds. Firstly, simulations of five kinds of lifters (triangular, trapezoidal, rectangular, ladder and hemispherical) were set up. The results were as follows: when the rectangular lifter was selected as mill liner, the ball mill efficiency was significantly high. The breaking performance of the hemispherical lifter and the ladder lifter was poor, because the main pattern of motion was grinding rather than impact breakage. Secondly, the effects of the height